SUPPORTING FRATERNITIES AND SORORITIES IN THE CONTEMPORARY ERA : advancements. (Education Ser., 2019)
Supporting Fraternities and Sororities in the Contemporary Erais inspired by sustained and reoccurring professional conversations and scholarship that have suggested that not just change is necessary, but that there ought to be a fundamental shift towards reconceptualizing the construct of fraternities and sororities. The co-editors curate work from scholars and noteworthy practitioners from across higher education to provide an imperative text that reflects the complexity and expansiveness by addressing diversity, programming, and support approaches. This text commences with the understanding.